VOCABULARY ACQUISITION FOR YOUNG LEARNERS THROUGH SONGS - Hermida, Rita (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2019)
Teaching English for Young Learner has been broadly discussed in many academic writings. Young learner is closely regarded to have a massive memory which can be potentially filled by any information. This potential age makes linguist attract to know more about how a language can be absorbed by children. Many theories are then occurred which are mostly stated that even a foreign vocabulary is possible to be learnt by the children. However, different place may give a different result. By this point, here, the writer was interested in identifying further information how the vocabulary acquisition in young learners. The place taken in this study was one of kindergarten in Banda Aceh which had nine classes, and each class consisted of 20 children. The choice was referred to the some conditions which made the researcher interested, namely, most of the students were not from local area where most people spoke Acehness language; and most of the students had not ever been aboard nor stayed in a country where English was speoken. The result shows that most of teacher used song to introduce the foreign vocabulary to the children. The children would sing the song and dance together by acting out what the lyrics if the song stated. The atmosphere of the classroom was encouraging.